APPLICATION OF THE PULLEY TOWER TRAINING COMPLEX BY HIGHLY QUALIFIED ATHLETES WHO COMPLETE A SPORTS CAREER WITH INJURIES OF THE MUSCULOSKELETAL SYSTEM - Savelyeva, V.V.; Ponomarev, G.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of the use of a complex of special physical exercises on the Pulley Tower multifunctional simulator for the prevention and correction of the musculoskeletal system and spine, for highly qualified athletes who completed their sports career with injuries to the musculoskeletal system. Methods and structure of the study. The pedagogical experiment was conducted on the basis of the GYROTONIC studios in Moscow, the Moscow region and St. Petersburg for 12 months. The experiment involved highly qualified athletes (Master of Sports, International Master of Sports, Honored Master of Sports of Russia) involved in gymnastic sports (artistic gymnastics, artistic acrobatics, rhythmic gymnastics, figure skating) and sports games (hockey, volleyball, tennis). Age - from 15 to 27 years, in the amount of 92 people. Results and conclusions. As part of the experiment, it was revealed that the proposed set of exercises on the Pulley Tower multifunctional simulator slows down the deterioration of the musculoskeletal system and spine of athletes after the end of their sports career. Restores the motor symmetry of the musculoskeletal system and spine during rotational movements, tilts to the right - to the left.